2014
DOI: 10.1103/physrevc.89.044908
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of charge multiplicity asymmetry correlations in high-energy nucleus-nucleus collisions atsNN=200GeV

Abstract: A study is reported of the same-and opposite-sign charge-dependent azimuthal correlations with respect to the event plane in Au + Au collisions at √ s NN = 200 GeV. The charge multiplicity asymmetries between the up/down and left/right hemispheres relative to the event plane are utilized. The contributions from statistical fluctuations and detector effects were subtracted from the (co-)variance of the observed charge multiplicity asymmetries. In the mid-to most-central collisions, the same-(opposite-) sign pai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 86 publications
4
63
0
Order By: Relevance
“…Such a splitting was observed by the STAR collaboration [550][551][552] and appears to be in qualitative agreement with the theoretical predictions.…”
Section: Chiral Magnetic Effect In Heavy Ion Collisionssupporting
confidence: 83%
“…Such a splitting was observed by the STAR collaboration [550][551][552] and appears to be in qualitative agreement with the theoretical predictions.…”
Section: Chiral Magnetic Effect In Heavy Ion Collisionssupporting
confidence: 83%
“…Bzdak et al [149,150,151] showed that the measured correlation signal is in-plane rather than out-of-plane as would be expected from the CME. This was also concluded by the STAR experiment using the charge multiplicity asymmetry observable [108]. The authors [149,150,151] also showed that the global momentum conservation contributes significantly to the measured γ signal, and pointed out the importance to also measure the δ correlator (see Sect.…”
Section: Nature Of Charge-dependent Backgroundsmentioning
confidence: 56%
“…Due to finite multiplicity fluctuations, one can easily vary the shape of the measured particle azimuthal distribution in final-state momentum space. This measured shape is directly related to the v 2 backgrounds in the measured ∆γ correlator [108,156].…”
Section: Event-by-event V 2 Methodsmentioning
confidence: 87%
See 2 more Smart Citations